PERMOHONAN DISPENSASI NIKAH DI BAWAH UMUR DI PENGADILAN AGAMA NANGA PINOH PADA TAHUN 2020 - Hardayanti, Siti; Marluwi, Marluwi; Muzammil, Sa'dulloh (Al-Usroh, 2023)
This study aims to find out: The reasons for the application for exemption for underage marriage at the Nanga Pinoh Religious Court and the basis for the judge's considerations in examining and determining the case for the requesting for exemotion for underage marriage at the Nanga Pinoh Religious Court. The method used in this study is a qualitative method with the type of empirical juridical research. The primary data source used was interviews with the Judge and Registrar of the Nanga Pinoh Religious Court. The secondary data used are books, journals, previous theses, Law No. 1 of 1974, Law No. 16 of 2019, Supreme Court Regulation Number 5 of 2019, as well as the annual case report of the Nanga Pinoh Religious Court. Data collection techniques in the form of interviews, observation and documentation. Then the data analysis technique uses reduction, presentation and conclusion drawing. After all the data is collected, then its validity is checked using source triangulation. The findings of this study indicate that the Request for marriage exemption at the Nanga Pinoh Religious Court is caused by changes to the Marriage Law, then there are very urgent reasons such as having had sexual relations which led to pregnancy outside of marriage. Worried about the emergence of slander from the community, then the habits of some people. In handling the marriage dispensation, the Judge is guided by PERMA No. 5 of 2019 especially the best interests of the child, during the process of handling marriage exemption cases there are supporting factors such as clear regulations, awareness of the applicant's parents, as well as electronic litigation regulations. The inhibiting factors are that the applicant does not present the parties, the administrative requirements are incomplete, the size of the jurisdiction of the Nanga Pinoh Religious Court, the community does not understand technology, and there is a language barrier.